Responsabilité des employeurs et financement des maladies professionnelles - Cécile Durand; Nathalie Ferre (Perspectives Interdisciplinaires sur le Travail et la Santé)
The recognition of occupational diseases gives rise, in France, to a procedure – administrative and often judicial – long and complex with which the employers know how to deal to escape the financial consequences. The litigation of non-opposability, here analyzed, highlights the irrelevance of the juridical system, in case of cancer, notably because of the usually long latency between exposures and diseases occurrence and in case of fragmented professional histories. This litigation, which tends to put aside the employees, questions the link wanted by the legislator between compensation and prevention of occupational diseases. It invites to reflect on the extent of the irresponsibility, built by the legislator, which benefits the employers and calls for a reform.